The Effects of Retention Measures on Retirement Timing—Do Financial Crises Matter? - Midtsundstad, Tove; Hermansen, Åsmund (Frontiers in Sociology, 2019)
Abstract The combined effect of rising life expectancy and declining fertility has made ‘ageing’ a dominant topic on the policy agenda across Europe. With the aim of retaining older workers and facilitating longer working lives, offering retention measures, such as the possibility of phased retirement, additional leave and/or bonuses to older workers, has become a widespread strategy among Norwegian companies to combat voluntary early retirement. However, analyses do not find any overall effect of offering such retention measures, although some single measures like additional leave and bonuses seem to have reduced early retirement among older workers in Norway. The aim of this article is to examine whether the limited effect of companies’ retention measures on early retirement have been impacted by the financial crisis of 2007/8. Our hypothesis is that the effect of companies’ retention measures on early retirement will be less if companies were affected by the financial crisis of 2007/08. Although most companies affected by the crisis of 2007/08 still offers retention measures, the financial hardship following the crisis may force some to priorities to cut cost and reduce staff, which may in turn lead to earlier rather than delayed retirement among their older employees. In order to investigate whether the effects of retention measures on early retirement vary between individuals in companies affected by the financial crisis of 2007/08 or not, we use data from a survey carried out among a representative sample of Norwegian companies in 2010 combined with individual register data on all employees in these companies in the period 2000-2010. Using individual fixed-effects in combination with a linear probability model we did not find that the financial crisis of 2007/08 impact on retention measures overall effects on early retirement. However, working in a company affected by the financial crisis of 2007/08 seem to reduce bonuses and extra days offs’ effect on early retirement among private sector employees; although the effects were not statistically significant. Hence it indicates, as expected, that the effect of retention measures on early retirement in the private sector are vulnerable to changes in companies’ performance and the overall market situation.